The Role of Moodle Software among Medical Students During Distance Learning - Oleksandr I. Fedіv; Inna O. Buzdugan; Volodymyr V. Vivsianyk; Iryna V. Prysіazhniuk; Vasyl P. Prysyazhnyuk (Mukachevo State University, 2021)
The study of the role of Moodle software among medical students is relevant, as distance learning is now new in terms of learning, processing, and teaching educational material online. The representation of new (latest) informative data using Moodle during distance learning contributes to and increases the level of students' knowledge. Moodle software is a valuable resource that presents an archive of educational (scientific) materials to students and teachers with unlimited access. The study is aimed at determining the role of Moodle for medical students during distance learning based on a theoretical review of the literature. Three stages of methodological justification were proposed as the basis for this study. At the first stage of the study, Moodle software was characterised; during the second - the role of distance learning was defined; third - the quality of medical students' training during distance learning through the use of innovative technologies, namely Moodle, was assessed. The study substantiates the significant role of Moodle and distance learning: understanding the goals of learning, gaining a significant "baggage" of knowledge, the latest information and access to resources, self-learning, self-improvement, and development of a "doctor" personality. The expediency of using the software among medical students is proved, taking into account the structure, logic, constant updating of materials, direct assessment of the student using test tasks and practical classes. Using Moodle software during distance learning, a medical student independently and consciously focuses on pathology based on the acquired knowledge, clearly and reasonably makes a preliminary conclusion (diagnosis) with subsequent appropriate treatment. The combined use of Moodle software and highly qualified teachers improve the quality of education and guide the medical student to focus on the study material and improve one's practical skills with the presented materials and visual aids